Human γδ T‐cell receptor repertoire is shaped by influenza viruses, age and tissue compartmentalisation - Sneha Sant; Misty R Jenkins; Pradyot Dash; Katherine A Watson; Zhongfang Wang; Angela Pizzolla; Marios Koutsakos; Thi HO Nguyen; Martha Lappas; Jane Crowe; Tom Loudovaris; Stuart I Mannering; et al. (Clinical & Translational Immunology, 2019)
Abstract Background Although γδ T cells comprise up to 10% of human peripheral blood T cells, questions remain regarding their role in disease states and T‐cell receptor (TCR) clonal expansions. We dissected anti‐viral functions of human γδ T cells towards influenza viruses and defined influenza‐reactive γδ TCRs in the context of γδ‐TCRs across the human lifespan. Methods We performed 51Cr‐killing assay and single‐cell time‐lapse live video microscopy to define mechanisms underlying γδ T‐cell‐mediated killing of influenza‐infected targets. We assessed cytotoxic profiles of γδ T cells in influenza‐infected patients and IFN‐γ production towards influenza‐infected lung epithelial cells. Using single‐cell RT‐PCR, we characterised paired TCRγδ clonotypes for influenza‐reactive γδ T cells in comparison with TCRs from healthy neonates, adults, elderly donors and tissues. Results We provide the first visual evidence of γδ T‐cell‐mediated killing of influenza‐infected targets and show distinct features to those reported for CD8+ T cells. γδ T cells displayed poly‐cytotoxic profiles in influenza‐infected patients and produced IFN‐γ towards influenza‐infected cells. These IFN‐γ‐producing γδ T cells were skewed towards the γ9δ2 TCRs, particularly expressing the public GV9‐TCRγ, capable of pairing with numerous TCR‐δ chains, suggesting their significant role in γδ T‐cell immunity. Neonatal γδ T cells displayed extensive non‐overlapping TCRγδ repertoires, while adults had enriched γ9δ2‐pairings with diverse CDR3γδ regions. Conversely, the elderly showed distinct γδ‐pairings characterised by large clonal expansions, a profile also prominent in adult tissues. Conclusion Human TCRγδ repertoire is shaped by age, tissue compartmentalisation and the individual's history of infection, suggesting that these somewhat enigmatic γδ T cells indeed respond to antigen challenge.